Stroke Therapy Academic Industry Roundtable (STAIR) Recommendations For Extended Window Acute Stroke Therapy Trials - Saver, Jeffrey L. (2009)
The Stroke Therapy Academic Industry Roundtable (STAIR) meetings focus on helping to advance the development of acute stroke therapies. Further extending the time window for acute stroke therapies is an important endeavor for increasing the number of stroke patients who might benefit from treatment. The STAIR group recommends that future extended time window trials initially should focus on selected patient groups most likely to respond to investigational therapies and that penumbral imaging is one tool that may identify such patients. The control group in these trials should receive best locally available medical care; if regulatory approval for intravenous (i.v.) tPA is extended to 4.5 hours, then tPA will become the most appropriate comparator in trials conducted within this time window. In future well-designed extended window clinical trials randomization is appropriate and should not be precluded by using unproven treatment with intra-arterial (i.a.) thrombolysis or mechanical devices. For proof of concept, extended time window, phase II trials of i.v. thrombolysis or mechanical devices in which early recanalization/reperfusion is the primary endpoint, rescue therapy/bailout treatment with i.a. thrombolysis or devices may be acceptable. Statistical considerations and definitions of successful recanalization/reperfusion are suggested for these trials.